If 3sinx + 4cosx = 5, then 4sinx - 3cosx =....???

  1. 0

  2. -5

  3. 1/5

  4. 5

plz explain me in detail... how to do questions like this... 

3 years ago


Answers : (2)


ANS    3sinx+4cosx=5

     => 3/5 sinx +4/5 cosx = 1

     let cosA=3/5   => sinA=4/5

     =>  cosAsinx + sinAcosx = 1

     =>  sin(x+A) = 1


       4sinx - 3cosx

  =   5(4/5sinx - 3/5 cosx)     [multipying numerator and denominator by 5]

  =   5(sinAsinx - cosAcosx)

  =   -5{cos(x+A)} = -5[root{1-(sin(x+A)^2)}] = -5 x 0 = 0          Ans 0


TRICK: if asinx+bcosx is given then multiply numerator and denominator by root(a^2 +b^2)

            this method is useful  in many questions 



 PLEASE       APPROVE       MY       ANSWER       IF       YOU       LIKE       IT


3 years ago


Squaring on both sides.

(3sinx+4cosx) 2 = 25

9sin2x +16 cos2x+24sinxcosx=25

9(1- cos2x)+16(1- sin2x)+ 24sinxcosx=25

9-9 cos2x+16-16 sin2x+24sinxcosx=25

25-9 cos2x-16 sin2x+24sinxcosx=25

9 cos2x+16 sin2x-24sinxcosx=0

(3cosx-4sinx) 2 = 0



one year ago

Post Your Answer

More Questions On Trigonometry

Ask Experts

Have any Question? Ask Experts
Post Question
Answer ‘n’ Earn
Attractive Gift
To Win!!!
Click Here for details
Give solution to the attached problem
Ans: Thanks & Regards Jitender Singh IIT Delhi askIITians Faculty
Jitender Singh 13 days ago
solve for x sin3x *sin(cube) x +cos3x *cos(cube) x=0
Hello Student, sin3x *sin^3 x +cos3x *cos^3 x=0 tan3x*tan^3x=0 =>tan3x=0 union tan^3x=0 =>3x=n*pi union x=n*pi
Arun Kumar 10 days ago
please give some easy method as i am in class 11 th this iss going above my head or can u just explain it
rashmi 23 hours ago
Value of a for which the given equation logx/loga = a^a^x has one solution..
Log x/log a= a^a^x x = a^a^a^x There is one possible solution when a= 1 Hence x = 1^x x=1 is the solution... Thanks Bharat Bajaj Askiitians faculty
bharat bajaj one month ago
Hi bharat bajaj for a=1 LHS would’t be defined because log(a)=0 !!!!!
Arun Kumar one month ago
Solve this question sir please
Ans: ….....(1) Put this in (1), we have
Jitender Singh 11 days ago
If the equation x^2 – x – p =0 and x^2 - 2xp - 12 =0 have a common root ,find it
x^2-x-p=0; p = (-x^2 +x) substitute p in 2 nd equation x^2-2x(-x^2+x)-12=0 2x^3-x^2-12=0 solving this eqn we get x = 2 and other roots are unreal so, the common root is 2
A person goes to office either by car, scooter, bus or train probability of which being 1/7 , 3/7 , 2/7 and 1/7 respectively. Probability that he reaches office late, if he takes car,...
Hello Student, P(C)=1/7 P(S)=3/7 P(B)=2/7 P(T)=1/7 I be the event of him reaching in time. P(I/C)=7/9 P(I/S)=8/9 P(I/B)=5/9 P(I/T)=8/9...
Arun Kumar 14 days ago
View all Questions »